Characterization of aarA, a pleiotrophic negative regulator of the 2'-N-acetyltransferase in Providencia stuartii. - Rather, P N (1994)
We have utilized transposon mutagenesis to obtain insertional mutations in Providencia stuartii that activate the chromosomal aac(2')-la gene. Two closely linked mini-Tn5Cm insertions were obtained in a locus designated aarA, and a single insertion was obtained in a separate locus, aarC. Nucleotide sequence analysis, complementation studies, and localization of the sites of mini-Tn5Cm insertion have allowed the identification of the aarA coding region. The deduced AarA protein had a molecular mass of 31,086 kDa and displayed characteristics of an integral membrane protein. A strain deleted for the aarA gene by allelic exchange showed at least a fourfold increase in the accumulation of aac(2')-la mRNA and an eightfold increase in aminoglycoside resistance. Mutations in aarA were pleiotrophic and also resulted in loss of pigmentation and a deficiency in cell separation during division.